2011
DOI: 10.1111/j.1365-2109.2011.02848.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofloc technology application as a food source in a limited water exchange nursery system for pink shrimp Farfantepenaeus brasiliensis (Latreille, 1817)

Abstract: In a 30-day experiment, Farfantepenaeus brasiliensis PL 25 (25 AE 10 mg;17.9 AE 1.6 mm) were raised in nine circular £oating cages with a stocking density of 1000 shrimp m À 3 . Three treatments were evaluated:(1) culture in BFT system plus a commercial feed supply (BFT1CF); (2) culture in BFT system without feed supply (BFT) and (3) culture in clear water with feed supply (control). Post-larvae (PL) ¢nal weight (218.9, 236.5 and 176.0 mg, for BFT1CF, BFT and control respectively), ¢nal biomass (17.9, 15.7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
197
2
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(243 citation statements)
references
References 43 publications
(115 reference statements)
24
197
2
20
Order By: Relevance
“…According to the same study, growth and survival was not affected by stocking density (2500 vs 5000 PL/m 2 ), therefore greater production outputs were achieved at the higher density. Furthermore, in [37] was found that F. brasiliensis postlarvae grow similarly with or without pelletized feed in biofloc conditions during 30-d of nursery phase, which was 40% more than conventional clear-water continuous exchange system.…”
Section: Applications In Aquaculture 41 Nursery and Grow-outmentioning
confidence: 95%
See 2 more Smart Citations
“…According to the same study, growth and survival was not affected by stocking density (2500 vs 5000 PL/m 2 ), therefore greater production outputs were achieved at the higher density. Furthermore, in [37] was found that F. brasiliensis postlarvae grow similarly with or without pelletized feed in biofloc conditions during 30-d of nursery phase, which was 40% more than conventional clear-water continuous exchange system.…”
Section: Applications In Aquaculture 41 Nursery and Grow-outmentioning
confidence: 95%
“…vannamei [44,48], P. monodon [51], F. paulensis [15,46], F. brasiliensis [37,52] and F. setiferus [34]. The primary advantage observed is related to a better nutrition by continuous consumption of biofloc, which might positively influence grow-out performance a posteriori [53], but was not always the case [54].…”
Section: Applications In Aquaculture 41 Nursery and Grow-outmentioning
confidence: 99%
See 1 more Smart Citation
“…it is available as a source of food supplement for cultured shrimp (Hari et al 2004;Arnold et al 2009;Ballester et al 2010), and offer essential in situ nutrients, such as protein (Emerenciano et al 2012), lipid (Wasielesky et al 2006), amino acids (Ju et al 2008) and fatty acids (Izquierdo et al 2006;Ekasari et al 2010). Biofloc biomass in the culture system that is consumed by cultured shrimp and digested, may compensate a significant amount of protein demand, and consequently reduce the quantity of fish meal (FM) required (Burford et al 2004;Crab et al 2010;Hari et al 2004;Wasielesky et al 2006;.…”
mentioning
confidence: 99%
“…Biofloc enhances ingestion rate, nutrient absorption, and assimilation, and provides a complete source of cellular nutrition (Tacon et al 2002). Broodstock diets fortified with biofloc supplementation improve reproductive performance in terms of fecundity, spawning, and egg biochemical composition in Farfantepenaeus duorarum and L. Vannamei (Emerenciano et al 2012a(Emerenciano et al , 2014. Tilapia culture inactivated suspension ponds indicated that the fish grew well on low-protein feed (Avnimelech 1999;Milstein et al 2001).…”
Section: Nutritional Composition Of Bioflocsmentioning
confidence: 99%